2017
DOI: 10.1186/s12885-017-3629-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GPR155 as a prognostic factor after curative resection of hepatocellular carcinoma

Abstract: BackgroundMolecular biomarkers capable of predicting recurrence patterns and prognosis are helpful for risk stratification and providing appropriate treatment to patients with hepatocellular carcinoma (HCC). In this study, we focused on G protein-coupled receptor 155 (GPR155), a cell surface signaling protein, as a candidate biomarker.MethodsWe analyzed GPR155 expression, DNA methylation, and copy number in HCC cell lines. The clinical significance of GPR155 expression was evaluated using 144 pairs of surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This phenotype was similar to what appeared in bone morphogenetic protein (BMP) signaling gain-of-function experiments [78]. GPR155 has also been linked to a number of different cancers [79,80].…”
Section: Otherssupporting
confidence: 77%
“…This phenotype was similar to what appeared in bone morphogenetic protein (BMP) signaling gain-of-function experiments [78]. GPR155 has also been linked to a number of different cancers [79,80].…”
Section: Otherssupporting
confidence: 77%
“…The key gene GPR155 in the blue module has also been extensively studied in cancers. In addition to its role as a biomarker in GC, the downregulation of GPR155 was reported as significantly associated with more aggressive HCC phenotypes including high preoperative α-fetoprotein, poor differentiation, serosal infiltration, vascular invasion, and advanced disease stage (Umeda et al, 2017). The presence of GPR155 in multiple gene pairs suggest it might be a crucial regulatory gene in GC and this offers clues for carrying out its further research in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…GPR155 encodes G protein-coupled receptor 155, and reported that mutations in this gene may be associated with autism ( 59 , 60 ). Although there has been a report that GPR155 expression is suppressed in neoplasm of the thyroid, hepatocellular carcinoma, and gastric cancer, implying a tumor suppressive function for this gene, the resistant role in lung cancer, however, was not reported ( 61 , 62 ). In the COSMIC, we found that GPR155 I357S mutations were estimated as pathogenic (score 0.99) and patients with this gene alteration showed poor prognosis compared those with unaltered patients.…”
Section: Discussionmentioning
confidence: 99%